(untitled) (Journal of Scientific Research, 2014)
Fermenting foods can make poorly digested, reactive foods into health giving foods. The process of fermentation destroys many of the harmful microorganisms and chemicals in foods and adds beneficial bacteria. These bacteria produce new enzymes to assist in the digestion. Foods that benefit from fermentation are soy products, dairy products, grains, and some vegetables. The beneficial effect of fermented food which contains probiotic organism consumption includes: improving intestinal tract health, enhancing the immune system, synthesizing and enhancing the bioavailability of nutrients, reducing symptoms of lactose intolerance, decreasing the prevalence of allergy in susceptible individuals, and reducing risk of certain cancers. This article provides an overview of the different starter cultures and health benefits of fermented food products, which can be derived by the consumers through their regular intake. Keywords: Fermentation; Fermented food; Starter cultures; Probiotics; Nutritional benefits. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.16530 J. Sci. Res. 6 (2), 373-386 (2014)